Fabrication of an ion-enhanced low-temperature tolerant graphene/PAA/KCl hydrogel and its application for skin sensors. Issue 12 (8th March 2023) - Wang, Yaoyao; Zhu, Longhang; Kong, XiangYu; Lu, Haimei; Wang, Chao; Huang, Yong; Wu, Min
Abstract : A multi-crosslinking network is well-designed using a facile strategy for the fabrication of a low-temperature tolerance hydrogel that exhibits excellent conductivity (0.8 S m −1 even at −80 °C) and sensitivity when applied in sensors at −20 °C. Abstract : Flexible sensors based on conductive hydrogels show great potential in wearable displays and smart devices. However, a water-based hydrogel inevitably freezes or loses its conductivity under extremely cold temperatures, leading to inadequate fulfillment of sensor performance. Herein, a well-designed strategy is proposed for fabricating a low-temperature-tolerant water-based hydrogel for sensor applications. By immersing a multi-crosslinking graphene(GO)/polyacrylic acid (PAA)-Fe 3+ hydrogel into a KCl solution, an ion-enhanced conductive (GO/PAA/KCl) hydrogel is obtained with excellent conductivity (24.4 S m −1 at 20 °C; 16.2 S m −1 at −20 °C; 0.8 S m −1 at −80 °C) and outstanding antifreezing properties. The conductive hydrogel also possesses good mechanical properties with a fracture stress of 2.65 MPa and an elongation at break of 1511% and maintains its flexibility even at −35 °C. Then, a strain sensor is assembled to monitor the human motion at 20 °C and the movement of a wooden mannequin at −20 °C. Under both conditions, the sensor presents high sensitivity (GF = 8.66 at 20 °C, 7.93 at −20 °C) and good durability (300 cycles under 100% strain). Consequently, the anti-freezing ion-enhanced hydrogel will meet the needs of flexible sensors designed for intelligent robots, health monitoring, etc ., which have to work in cold regions or extreme climates.